Research on the effect of Market Mechanism for Industrial Energy Conservation. Issue 1 (February 2021) - Guo, Huiting; Wang, Bo; Jin, Chenhong
Abstract: Over the years, China' s energy conservation practices has relied on government intervention, that is, the energy efficiency of enterprises has been improved by means of administrative orders and government regulation, but the endogenous power of energy conservation has not been effectively stimulated. Since the 12th Five-Year Plan period, with the improvement of enterprises' understanding of energy conservation, the government has gradually faded out from its powerful position during the 11th Five-Year Plan period and more attention has been paid to enterprises' dominant position in energy conservation. The Third Plenary Session of the 18th Central Committee of the CPC put forward that the market shall play a decisive role in the allocation of resources and the energy conservation shall give full play to the role of market mechanisms. Moreover, it also proposed to create a multi-benefit market environment, improve enterprises ' enthusiasm in energy conservation, actually benefit the enterprises in energy conservation and make the energy conservation a conscious action of enterprises by promoting contract energy management system, carrying out carbon emissions permit trading, implementing power demand side management and using fair and transparent market means.